A canção popular brasileira como possibilidade do filosofar em sala de aula - Lopes, Deyvison Ronny da Silva (2022)
This dissertation has as its theme the connection between the Brazilian popular songbook and Philosophy in High School. The present research arose when looking for a philosophy teaching strategy in high school that recognized the difficulties pointed out by students in reading and interpreting philosophical texts. We start from the following problem: How can Brazilian popular song become a strategy to teach Philosophy and lead students to philosophize at school? How can song stimulate philosophical reflection? What is the possible interface of a philosophy teaching methodology based on philosophical problems with music as an artisticcultural text coming from the student context? Therefore, we developed a practice of reading and interpreting philosophical texts using songs from the Brazilian popular songbook. The proposal was to look for relationships and interrelationships between Brazilian popular song and philosophical texts through a didactic that promotes philosophical teaching and allows an active participation of students in classes with philosophical texts. It also seeks to present some possibilities of approximation between the songs of the Brazilian popular songbook and the Teaching of Philosophy in Basic Education for a more attractive teaching. As a route, we approach aspects of Philosophy teaching, the role of the teacher, students and objectives when teaching Philosophy. This research was guided by a case study, whose data source consisted of the analysis of materials produced by students during Philosophy classes in High School, applied in a virtual way due to the SarsCoV-2 (COVID 19) pandemic which began in 2019. As a theoretical framework to discuss Philosophy Teaching, the authors Antoni Zabala (2010) Antônio Joaquim Severino (2009), Celso Favaretto (1995), Guillermo Obiols (2002), Silvio Gallo (2012) were used. , the authors were Lídia Maria Rodrigo (2009) and Renata Aspis (2009). On teaching using songs, we have the contributions of Charles Feitosa (2004), Martins Ferreira (2008) José Geraldo de Moraes (2000) and Marcos Napolitano (2002). With the interaction between Philosophy and the Brazilian popular songbook, I present some reflections on how Philosophy and Art are interconnected, how this interaction contributes to the development of teaching and learning, making classes more attractive and, thus, promoting thinking critical in the relationship between students and the songs they consume. The main idea defended here is that popular songs can make the contents, the philosophical texts of the history of Philosophy and the themes of Philosophy more attractive to the extent that we can make an analysis of the contents, and that this can be done in the schools, in the discipline of Philosophy. The challenge is to use the songs as a means and not as an end, starting from the usual signs of our time to try to conquer the opening for philosophical questioning. And as a final product, we present a pedagogical proposal, which is a didactic unit, in which it is possible to experience the connection between Philosophy and Brazilian popular songs.